Social representations of odors: case study in the Ñuble region, Chile (2019–2023) - Parada-Ulloa, Marcos; Bozo Marambio, Jorge; Moreno-Leiva, Germán; Vásquez-Burgos, Karina; Vega Gutiérrez, Oscar; Mansilla-Sepúlveda, Juan; Larez-Hernández, José; Salazar Cayuleo, Héctor; Morales Ojeda, Ismael (Frontiers in Social Psychology, 2024)
The objective of this article is to analyze the social representation of odors and the identity of the population in the Ñuble region between 2019 and 2023. It investigates how industrialization and urban and rural development have altered the olfactory landscape in the Ñuble region. This allows for an understanding of how changes in the physical environment affect the representation of odors, and how these, in turn, impact the daily lives of residents. Using an interpretive approach and case studies, the analysis of primary sources is categorized into two areas: public policy regarding odors and the situation of odors in the cities of Chillán Viejo and Chillán.The conclusion is that odors are not only sensory experiences but also social phenomena that influence the perception of the environment and community relationships.